2017
DOI: 10.5194/bg-14-3851-2017
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of root growth under mild water stress increases water use efficiency without reducing yield in maize

Abstract: Abstract. A large yield gap exists in rain-fed maize (Zea mays L.) production in semi-arid regions, mainly caused by frequent droughts halfway through the crop-growing period due to uneven distribution of rainfall. It is questionable whether irrigation systems are economically required in such a region since the total amount of rainfall does generally meet crop requirements. This study aimed to quantitatively determine the effects of water stress from jointing to grain filling on root and shoot growth and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Similar to our results, it was reported that the yield WUE of dehydration-tolerant variety was higher than the dehydration susceptible variety and there was no varietal difference of WUE in wheat (Thapa et al, 2018). Also, the high yield WUE values of maize were also associated with their high grain yields, resulting from the high number of grains per plant (Cai et al, 2017;Nagore et al, 2017).…”
Section: Factors In Relation To Water Use Affecting Dehydration Tolersupporting
confidence: 90%
“…Similar to our results, it was reported that the yield WUE of dehydration-tolerant variety was higher than the dehydration susceptible variety and there was no varietal difference of WUE in wheat (Thapa et al, 2018). Also, the high yield WUE values of maize were also associated with their high grain yields, resulting from the high number of grains per plant (Cai et al, 2017;Nagore et al, 2017).…”
Section: Factors In Relation To Water Use Affecting Dehydration Tolersupporting
confidence: 90%
“…Peanut ranks second the most important grain legume food only after soybean (Maingi et al., 2001) and is one of the five most important oilseed products. In semi‐arid environment, such as Liaoning China, rainfed maize frequently suffers drought during growing season (Cai et al., 2017), and sole peanut causes wind erosion because of loosening surface soil at harvest time (Tan et al., 2015). Therefore, farmers grow maize and peanut as a strip intercrop, normally two rows maize intercropped with four rows peanut.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other months, the simulation error of jujube and cotton during the middle and late stages of growth (August to September) increased abnormally during the three years. This may be due to the increased water absorption capacity of the root system caused by severe water stress [34,35], which affects the simulation accuracy. The determination and modification of water stress are involved in the dual crop coefficient method, which mainly depends on the soil water consumption coefficient p. For this purpose, based on the 2016 soil moisture content measurement, the soil water consumption coefficient p was calculated.…”
Section: Data Processing and Analysismentioning
confidence: 99%